The Effectiveness of Awig-Awig as A Strategy to Protect DMCA Gili Sulat and Gili Lawang - Kartini, Fitriah (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2019)
This study was carried out in the District Marine Conservation Area (DMCA) of Gili Sulat and Gili Lawang, East Lombok. DMCA of Gili Sulat and Gili Lawang have established by Co-Fish Project of Marine Affairs and Fisheries Ministry of Indonesia in 2004 as part of participative management sustainability to coastal resources. The aim of establishing DMCA is to decrease destructive fishing activities such as bombing and poisoning that has been practices for long time. In this study, data were collected through semi structure questionnaires, personal interview, participant observation, document reviews, and life history. Discussions were held with the fishermen in Sugian Village, fisheries management committee of DMCA, local communities who living in Sugian Village and government in village, local and regional level. In order to analyze the findings, an analyzing of legal and institutional arrangements is used combining with the theories of legal pluralism and property rights. The study revealed that there are two laws coexist in DMCA as state laws and customary laws called awig-awig. State laws are covered legal status of DMCA as property of state where local government has authority to manage it. Meanwhile, customary laws are more to control people behaviors towards DMCA. Moreover, a fisheries management committee (KPPL) has formed by government to enforce day-to-day awig-awig practices towards DMCA and has its authority to invoke sanctions for rule breaking. Because of this, several problems arose in Sugian Village concerning to DMCA. This required better management of coastal resources where planning should be come from and involve grass root level. Finally, the study revealed that management of DMCA should be reinforced to all parties particularly on communities’ level, so that the problem foci can be clear for all.